Implementation of Project Activities in the System of StudentCentered Learning - I. N. Mishin (Высшее образование в России)
The article addresses the educational project activities implementation at universities as part of the student-centered learning and a means to raise the effectiveness of students’ professional training. The article provides a critical comparison of the basic elements and features of project activities and SCL. The author proposes a three-tier system of teacher – student – teacher and a methodology for project activities implementation, taking into account the basic principles of SCL. In accordance with the developed system, at the first stage, the teacher organizes the student’s activities on the project including his/her discussing the topic, problem, goal, determining their own requirements for the implementation of the project and individual tasks. At the second stage, the methodology determines the organization of students’ self-governing work on the project, taking into account their personal qualities and experience. An active management of self-governing work enables to build an individual educational trajectory of a student, guide his/her personal development. At the third stage, the methodology determines the teacher’s activities to foster mastering the competencies by the students. These activities are necessarily based on partnership interaction and exchange of views between the teacher and students, the student’s personal critical assessment of the project results and its comparison with the work of other students. The author suggests to positively evaluate incomplete or erroneous results in case the way and method to achieve the assigned tasks were correct and use transparent, objective and understandable for students criteria in assessing the results of his work.